Strategic Directions for Increasing the Share of Renewable Energy Sources in the Structure of Energy Consumption - Kapitonov, Ivan A.; Voloshin, Vladimir I. (International Journal of Energy Economics and Policy, 2017)
In recent decades, the European energy sector is transforming due to the growing demand for electricity and increased requirements for ensuring the continuity of supply. In the European Union, almost 50% of energy consumption is provided through energy imports. One of the main conditions for the continuity of supply is the diversification of their sources, considered as an important prerequisite for energy security. The EU government has serious hopes for the development of alternative energy and believes that in the future "green" energy will play a significant role in the structure of energy consumption. The object of this study is renewable energy sources. The subject of the research is the problems of increasing the share of renewable energy sources in the structure of energy consumption. Keywords: electric power industry, alternative energy, the electricity consumers. JEL Classifications: K32, O13, P48